Open access: The global scene. Issue 1 (2014) - Assefa, Shimelis; Rorissa, Abebe; Matusiak, Krystyna; Gelaw, Daniel; Helge, Kris
ABSTRACT: Significant achievements have been scored regarding Open Access (OA) and its worldwide adoption. The increasing numbers in the availability of OA repositories and journals (refereed and otherwise); publishers that embraced OA in different forms; universities and colleges that adopted OA as a matter of policy; and funding agencies that require authors and researchers to deposit their work in openly accessible digital repositories are all clear indications of the widespread adoption of OA practices. However, the practices are not well coordinated, largely project‐based, and dictated by institutional circumstances. For the sake of disseminating and preserving scholarly publications and other forms of research outputs well into the future, it is critical that a consistent and uniform policy and technical framework that addresses the needs and concerns of all relevant stakeholders involved be adopted. Members of this panel will review the global OA practices and suggest ideas for the implementation of an international infrastructure that supports and sustains the future of open scholarly communication. Sponsors SIG III and SIG IFP